SAWFIER: A Solar-Powered Reverse Osmosis Desalinator for Clean Water Solutions in Coastal Communities - Fikriansyah, Dzaky Aqillah; Damardhi, Sahi Rafael; Jimmy, Jimmy (Universitas Tribhuwana Tunggadewi Malang, 2025)
Access to clean water remains a critical challenge for coastal communities worldwide, exacerbated by seawater intrusion, population growth, and insufficient infrastructure. Indonesia, as an archipelagic nation with extensive coastlines, faces significant disparities in clean water access, particularly in rural and underserved regions. This research develops and evaluates SAWFIER (Salt Water Purifier), a solar-powered desalination system utilizing the Reverse Osmosis (RO) principle, designed to provide sustainable clean water solutions in coastal areas. Performance testing was conducted using seawater with an initial salinity of 10,000 ppm. Key parameters, including salinity, pH, and water volume, were monitored at 5-minute intervals over a 120-minute operational period. The results demonstrated a consistent reduction in salinity to 1.36 ppt at the end of the test, with optimal performance observed up to 95 minutes, maintaining salinity levels below 1 ppt. The system generated an average daily energy output of 820.25 Wh from two 100 Wp solar panels, exceeding its energy consumption of 520.2 Wh, resulting in a surplus of 300.05 Wh. These findings highlight SAWFIER’s potential as an energy-efficient, scalable, and eco-friendly solution for addressing clean water scarcity in coastal regions. Despite challenges such as membrane fouling during prolonged operations, the system demonstrates strong alignment with Sustainable Development Goal (SDG) 6, emphasizing universal access to clean water and sanitation.